Genetic diversity in Eddoe Taro (Colocasia esculenta var. antiquorum) from Indonesia based on morphological and nutritional characteristics - Delvi Maretta; Sobir Sobir; Is Helianti; Purwono Purwono; Edi Santosa (Society for Indonesian Biodiversity, 2020)
Abstract. Maretta D, Sobir Helianti I, Purwono, Santosa E. 2020. Genetic diversity in Eddoe Taro (Colocasia esculenta var antiquorum) from Indonesia based on morphological and nutritional characteristics. Biodiversitas 21: 3525-3533. Low yield uniformity and quality due to genetic performance become negative incentives to farmers in Eddoe Taro production. However, genetic evaluation is rarely been reported in this taro type in Indonesia. In this study, 14 eddoe genotypes collected from different regions in Indonesia were evaluated to develop a diversity map for crop improvement and future breeding activities. The genotypes were planted in the open field from September 2018 to March 2019 at the experimental station belonging to LAPTIAB-BPPT, PUSPITEK at South Tangerang District, Indonesia. Morphological and nutritional characters were accessed on the shoot and underground parts. The genotypes exhibited variation in 38 out of 48 characters in which 12 quantitative characters were distinct including oxalate level. The study revealed three findings: (i) Characters related to growth and yield had high genotypic variance coefficients, i.e., sheath length, total petiole length, plant height, number of suckers, corm and cormels weight, (ii) Genotypes clustered into two separate groups as introduced and landraces, and (iii) Landraces had high genetic variation leading to speculation of high clonal variation. Considering the findings, accession S6, S7, S18, S30, and S36 are recommended for further studies in crop improvement purposes.